Adapting an evidence-based gender, livelihoods, and HIV prevention intervention with street-connected young people in Eldoret, Kenya. Issue 12 (2nd December 2019) - Embleton, Lonnie; Di Ruggiero, Erica; Odep Okal, Evans; Chan, Adrienne K.; Logie, Carmen H.; Ayuku, David; Braitstein, Paula
ABSTRACT: Despite being highly vulnerable to acquiring HIV, no effective evidence-based interventions (EBI) exist for street-connected young people (SCY) in low- and middle-income countries (LMICs). Therefore, this paper describes the research process of adapting an existing EBI in Eldoret, Kenya using a modified ADAPT-ITT model with a young key population. From May to August 2018 we adapted the combined Stepping Stones and Creating Futures interventions. We used community-based participatory methods, focus group discussions, and working groups with four Peer Facilitators and 24 SCY aged 16–24 years. At the inception of this project, a matched-savings programme was integrated into the intervention to further address structural drivers of HIV. Numerous adaptations came forth through the participatory process. Engaging SCY in the adaptation process ensured the programme was responsive to their needs, relevant to the street context, and respected their right to participate in the research process.